A rational approach to single, dual and triple therapy in COPD. Issue 4 (26th November 2015) - Calverley, Peter; Vlies, Ben
Abstract: The complexity of COPD treatment has increased over the last 5 years mainly because of the proliferation of drugs and delivery devices. In this paper, we will focus on currently available therapy used for maintaining patient well‐being rather than acute relief of symptoms. We propose a series of principles for rational therapy, and following a review of how currently available treatments perform in isolation and when compared with each other, we suggest an approach to aid the rational selection of the most appropriate treatment based on current evidence.